2022
DOI: 10.1155/2022/1322788
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 2 Family Member (ALDH2) Is a Therapeutic Index for Oxaliplatin Response on Colorectal Cancer Therapy with Dysfunction p53

Abstract: Oxaliplatin resistance is a major issue in the treatment of p53 mutant colorectal cancer (CRC). Finding the specific biomarkers would improve therapeutic efficacy of patients with CRC. In order to figure out the biomarker for CRC patients with mutant p53 access oxaliplatin, a Gene Expression Omnibus dataset (GSE42387) was used to determine differentially expressed genes (DEGs). The Search Tool for the Retrieval of Interacting Genes (STRING) and Cytoscape software were used to predict protein-protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Previously, we reported that ALDH2, the critical enzyme in the oxidative pathway in alcohol metabolism, is correlated with chemotherapeutic drug resistance. However, the low expression level of ALDH2 was associated with poor patient survival, and inhibiting ADH2 by daidzein increased oxaliplatin resistance in the CRC cell line with p53 mutation, HT29, but not in p53 wild‐type cell line, HCT 116 22 . In this study, we focused on the role of ALDH2 in CRC progression by inhibiting the enzymatic activity of ALDH2 by CVT‐116 and daidzein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that ALDH2, the critical enzyme in the oxidative pathway in alcohol metabolism, is correlated with chemotherapeutic drug resistance. However, the low expression level of ALDH2 was associated with poor patient survival, and inhibiting ADH2 by daidzein increased oxaliplatin resistance in the CRC cell line with p53 mutation, HT29, but not in p53 wild‐type cell line, HCT 116 22 . In this study, we focused on the role of ALDH2 in CRC progression by inhibiting the enzymatic activity of ALDH2 by CVT‐116 and daidzein.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low expression level of ALDH2 was associated with poor patient survival, and inhibiting ADH2 by daidzein increased oxaliplatin resistance in the CRC cell line with p53 mutation, HT29, but not in p53 wild-type cell line, HCT 116. 22 In this study, we focused on the role of ALDH2 in CRC progression by inhibiting the enzymatic activity of ALDH2 by CVT-116 and daidzein. Our results demonstrated that inhibiting ALDH2 by CVT-10216 significantly reduced HCT 116 and DLD-1 colon cancer cell migration and stemness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mogroside V anti-COVID-19/ovarian cancer action targets were obtained from the STRING ( 21 ) database to establish target–target function-related protein interactions with a minimum reciprocal value of 0.09. The results were imported into Cytoscape_v3.6.1 ( 22 ) to construct the mogroside V anti-COVID-19/ovarian cancer target-related protein–protein interaction (PPI) network.…”
Section: Methodsmentioning
confidence: 99%